SMART FARMING USING A SOLAR-POWERED AQUAPONICS SYSTEM FOR SUSTAINABLE FOOD PRODUCTION - Zainal Alam, Muhd Nazrul Hisham; Kamaruddin, Mohd Johari; Samsudin, Sani Amril; Othman, Raudhah; Mohammad Radzi, Nur Hanis; Emmanuel, Abioye Abiodun; Zainal Abidin, Mohamad Shukri (MJS, 2023)
This paper discusses the prospect of using solar energy for aquaponics operations. Aquaponic is a platform for farmers to grow fish and plants in the same unit simultaneously. The system is considered a sustainable and green technology. Aquaponics operation may be hampered by the necessity for pumps for continuous water recirculation and air supply within the system, especially if the unit is located far from any power outlet. Given that Malaysia is positioned at the equator and receives an average of 9 hours of sunlight per day throughout the year, with solar intensity as high as 1800–1900 kWh/m2, it is unquestionably a practical solution. This paper examines utilities of aquaponics platforms that can be supported by solar energy and describes equipment for setting up a suitable solar PV system for aquaponics operation. Possible integration of the Internet-of-Things (IoT) for remote monitoring of such solar-operated aquaponics units is also discussed. Analysis revealed that the production and growth rates of the crop and fish grown in the system were unchanged even when fully supplied with energy for 12 hours. The finding indicates the potential for using solar energy as alternative energy for the operation of the aquaponics unit. Aquaponic system particularly benefits farming activities in rural locations without electricity. Despite the high installation costs (a 100 W PV system might cost nearly RM 600), the technology offers long-term savings on electricity expenses and national grid installation fees. In conclusion, the project provided the idea of smart farming using aquaponics for the sustainable production of crops and fish utilizing clean, renewable solar energy.